2006
DOI: 10.1111/j.1572-0241.2006.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of CYP2C19 Polymorphisms on H. pylori Eradication Rate in Dual and Triple First-Line PPI Therapies: A Meta-analysis

Abstract: The impact of CYP2C19 polymorphisms on H. pylori eradication rates in studied populations appears clinically relevant in patients prescribed omeprazole as a component of their dual- or triple-drug therapy, whereas regimens that include lansoprazole or rabeprazole are unaffected. The choice of PPI and/or dose rather than CYP2C19 genotyping could be a more practical approach to assure the highest H. pylori eradication rates in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
1
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(126 citation statements)
references
References 36 publications
7
113
1
5
Order By: Relevance
“…The majority of studies have come from Asia where poor metabolizers are relatively common. The frequency of poor metabolizers is low in Western populations and although some reports have suggested that CYP2C19 genotypes may not be important in Western populations 39,40 . However, others have confirmed the phenomena of improved results with poor metabolizers 41 .…”
Section: Host Factors Influencing Treatment Successmentioning
confidence: 95%
“…The majority of studies have come from Asia where poor metabolizers are relatively common. The frequency of poor metabolizers is low in Western populations and although some reports have suggested that CYP2C19 genotypes may not be important in Western populations 39,40 . However, others have confirmed the phenomena of improved results with poor metabolizers 41 .…”
Section: Host Factors Influencing Treatment Successmentioning
confidence: 95%
“…In contrast, Caucasians have a higher prevalence rate of HomEM compared with Asians [142] . Accordingly, geographic differences should be considered in selecting doses or types of PPIs for H. pylori treatment since there is a significant difference between HetEM and HomEM (OR = 1.90; 95%CI: 1.38-2.60) in H. pylori eradication rate [143] . In additional subanalysis of individual PPIs revealed that omeprazole was influenced by the CYP2C19 genotype [143] .…”
Section: Is Tailored Therapy On the Horizon For H Pylori Treatment?mentioning
confidence: 99%
“…Accordingly, geographic differences should be considered in selecting doses or types of PPIs for H. pylori treatment since there is a significant difference between HetEM and HomEM (OR = 1.90; 95%CI: 1.38-2.60) in H. pylori eradication rate [143] . In additional subanalysis of individual PPIs revealed that omeprazole was influenced by the CYP2C19 genotype [143] . In another meta-analysis, successful eradication rates differed considerably between PM and HetEM (OR = 1.73, P = 0.002) and between PM and HomEM (OR = 2.79, P < 0.0001) and even between HetEM and HomEM (OR = 2.00, P < 0.0001) [144] .…”
Section: Is Tailored Therapy On the Horizon For H Pylori Treatment?mentioning
confidence: 99%
“…Several factors are reportedly associated with a decreased efficacy of H. pylori eradication therapy, including antibiotic resistance, CYP2C19 polymorphisms, MDR1 C3435T polymorphism, eradication duration, smoking, and probiotics. [23][24][25][26][27][28] Drug compliance was also found to be a risk factor of eradication failure. 12,29 To minimize the effects of these factors, we chose the same regimen with a 7-day duration in all the patients.…”
Section: Discussionmentioning
confidence: 99%